Method for producing high hardness wear resistant coating on low carbon steel surface based on decomposition of sic

CN116555754BActive Publication Date: 2026-10-30TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310553594.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-17
Publication Date
2026-10-30
Estimated Expiration
2043-05-17

AI Technical Summary

Technical Problem

采用该方法虽能将SiC熔化并分解,但由于过快的加热和冷却速度会使涂层不可避免的存在气孔、裂纹、成分偏析等问题,原位生成的硬质相种类单一,对涂层硬度和耐磨性的提升有限,且高温熔化方法往往会恶化钢基体的性能

Benefits of technology

1)本发明利用Ni基金属的催化作用,使SiC颗粒在远低于其熔点的温度下分解,原位生成多种类、多尺度的碳化物、硼化物和硅化物增强相,在固溶强化、细晶强化以及第二相强化的综合作用下,涂层硬度及耐磨性能均提升8~15倍。与激光熔覆等技术相比,本发明熔覆温度低,对基体的损伤作用小;原位生成的增强相具有热力学稳定、分布均匀、界面洁净、与涂层基体结合良好等优点,有效避免了外加增强相结合力差、偏聚等问题;多种类、多尺度的增强相结构可克服单一增强相的局限性,多种增强相间“取长补短、硬韧互补”对熔覆层产生“复合增强效应”,从而解决单一增强相与涂层基体磨损率不匹配和韧性降低等问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116555754B_ABST
    Figure CN116555754B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing a high-hardness wear-resistant coating on the surface of low-carbon steel based on SiC decomposition, and belongs to the technical field of surface modification. The method comprises the following steps: firstly, rust removal and cleaning treatment are performed on the surface of the low-carbon steel; then, an organic binder is brushed on the surface of the low-carbon steel, and SiC particles are uniformly sprayed on the surface; subsequently, NiCrSiBC alloy powder of two sizes is sprayed in sequence until the surface reaches the closest arrangement, and then the binder is brushed again and the alloy powder of the two sizes is sprayed again; finally, a vacuum heating device is used to perform high-temperature cladding on the treated sample at a temperature far below the melting point of SiC, and a high-hardness wear-resistant coating containing multiple reinforcing phases such as carbides, borides and silicides is obtained on the surface of the low-carbon steel after furnace cooling. The coating and the substrate are metallurgically combined, the coating has good compactness, the hardness and wear resistance of the surface of the low-carbon steel are greatly improved, and the application range of the low-carbon steel is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of surface modification technology, specifically a method for preparing a high-hardness wear-resistant coating on the surface of low-carbon steel based on SiC decomposition. Background Technology

[0002] Steel, due to its abundant raw materials, low price, excellent performance, and ability to be industrially produced, can better meet the various needs of national economic development, making it one of the most important engineering materials. Low-carbon steel is the most widely used steel grade in industrial production, frequently used in components for construction, vehicles, ships, petroleum, chemical, and power plant projects. Therefore, improving the comprehensive performance of low-carbon steel is of great significance. For a long time, people have been committed to developing high-performance steel materials, but these materials often suffer from problems such as complex production processes, high energy consumption, and high prices. It is well known that material damage and failure in service environments often begin on the surface. Low-carbon steel operates in complex and unique environments, and its low carbon content also leads to fatal defects such as low surface hardness and poor wear resistance, making it more prone to wear and failure, resulting in huge metal consumption and economic losses. To solve these problems, applying a high-hardness wear-resistant layer to the surface of low-carbon steel has become an effective and cost-effective technical means.

[0003] SiC possesses excellent hardness, strength, high-temperature oxidation resistance, and wear resistance, making it a superior wear-resistant material. It has been widely used in single-component wear-resistant coatings and composite coatings with other materials. However, SiC ceramic coatings suffer from difficulties in preparation and processing, as well as high brittleness, making them unsuitable for manufacturing large-size wear-resistant coatings. Furthermore, the significant difference in thermal expansion coefficients limits their integration with steel materials. In contrast, SiC particles have attracted widespread attention due to their similar excellent properties to SiC ceramics, along with their low cost and simple preparation. Currently, some researchers are using SiC particles as a reinforcing phase in composites with metals or alloys for wear-resistant layer preparation. This combination combines the advantages of a metal matrix (high toughness) and a ceramic phase (high strength, high wear resistance, and good high-temperature resistance), effectively improving the brittleness of single SiC ceramic coatings and reducing the difference in thermal expansion coefficients between the coating and the steel substrate.

[0004] The composite of SiC particles and metal significantly improves the hardness and wear resistance of coatings. However, wear-resistant layers with ceramic particles as the main reinforcing phase inevitably suffer from fatal drawbacks such as low particle adhesion, easy detachment, poor coating density, and fracture. To overcome these problems, some researchers have attempted to use high-temperature treatment methods such as laser cladding and thermal spraying to melt the SiC particles in the coating by heating to the melting point of SiC, thereby promoting the in-situ generation of new hard phases and indirectly improving the wear resistance of the coating. Simultaneously, the problem of particle detachment is also significantly mitigated. For example, Chinese invention patent CN202210939120.2 discloses an alloy powder for in-situ generation of TiC reinforcing phases and a cladding layer prepared using this powder. Laser cladding technology is used to clad a mixed powder containing Ti, SiC, and other elements onto the surface of high-chromium cast iron. Through in-situ generation technology, numerous fine and dispersed TiC reinforcing phase particles are generated during the solidification process of the cladding layer, thereby improving the hardness and wear resistance of the coating. Although this method can melt and decompose SiC, the rapid heating and cooling rates inevitably cause problems such as porosity, cracks, and component segregation in the coating. The in-situ generated hard phase is of a single type, which has limited effect on improving the coating's hardness and wear resistance. Furthermore, the high-temperature melting method often deteriorates the performance of the steel substrate. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the purpose of this invention is to provide a method for preparing a high-hardness, wear-resistant coating on the surface of low-carbon steel based on SiC decomposition. This method utilizes Ni-based metal catalysis to decompose SiC, generating various types and scales of reinforcing phases in situ within the coating. The resulting coating is dense and uniform in composition, effectively avoiding the problem of poor adhesion of added SiC particles, and significantly improving the hardness and wear resistance of the low-carbon steel surface.

[0006] This invention is achieved through the following technical solution: A method for preparing a high-hardness wear-resistant coating on a low-carbon steel surface based on SiC decomposition includes the following steps: (1) Surface pretreatment of low carbon steel: Grind the surface of low carbon steel with sandpaper to remove oxide layer and rust, and clean it with deionized water, acetone or alcohol to obtain a clean surface of low carbon steel substrate material. (2) SiC particle fixation: A layer of organic adhesive is brushed onto the surface of the low carbon steel substrate material, and then SiC particles are evenly sprayed onto the surface of the low carbon steel substrate material and bonded and fixed with the organic adhesive. (3) NiCrSiBC alloy powder fixation: Spray two types of NiCrSiBC alloy powder of different sizes onto the surface of the SiC particle layer until the surface is densest; then continue to brush on a layer of organic binder, and spray two types of NiCrSiBC alloy powder of different sizes again to achieve the densest arrangement. (4) High-temperature cladding: The treated low-carbon steel substrate material is placed in a vacuum heating device and clad at a temperature much lower than the melting point of SiC. (5) Post-treatment: After furnace cooling, the low carbon steel substrate material is quenched and tempered respectively, and finally a high hardness wear-resistant coating containing multiple reinforcing phases such as carbides, borides, and silicides is obtained on the surface of the low carbon steel substrate material.

[0007] As a preferred technical solution, in step (2), the particle size of SiC particles is 100 µm to 500 µm, and the proportion of SiC particle spraying amount in the total amount of SiC particles and NiCrSiBC alloy powder is 2 to 8 wt.%.

[0008] As a preferred technical solution, in step (3), the particle size of the large-size NiCrSiBC alloy powder is 50 µm ~ 700 µm, the particle size of the small-size NiCrSiBC alloy powder is 0.3 ~ 0.7 times that of the large-size alloy powder, and the proportion of NiCrSiBC alloy powder sprayed in the total amount of SiC particles and NiCrSiBC alloy powder is 92 ~ 98 wt.

[0009] As a preferred technical solution, in step (3), the NiCrSiBC alloy powder is composed of elements Ni, Cr, Si, B and C, wherein the Cr content is 5~10 wt.%, the Si content is 3~8 wt.%, the B content is 2~7 wt.%, the C content is 0.05~0.1 wt.%, and the Ni content is 74.9~89.95 wt.%.

[0010] As a preferred technical solution, in step (3), the densest arrangement means that no new large (small) NiCrSiBC alloy powder particle can be added between three or four adjacent large (small) NiCrSiBC alloy powder particles.

[0011] As a preferred technical solution, in step (4), the heat preservation temperature of the vacuum heating equipment is 1000~1150 ℃, and the heat preservation time is 5 min~40 min.

[0012] The technical principle of the method of the present invention is as follows: This invention employs vacuum cladding technology to clad a certain proportion of SiC particles and two sizes of NiCrSiBC alloy powder onto the surface of low-carbon steel at a temperature far below the melting point of SiC. Under the catalytic action of the Ni-based alloy, SiC completely decomposes. The decomposition products, C and Si, react fully with elements in the alloy during cladding and furnace cooling, forming various reinforcing phases such as carbides, borides, and silicides in situ within the coating. The abundance of C in the coating creates a significant C concentration difference between the coating and the low-carbon steel substrate, causing C to diffuse into the substrate and produce a carburizing effect, resulting in metallurgical bonding. The purpose of using NiCrSiBC alloy powder of two different sizes in this invention is that the smaller alloy powder can be used to fill the gaps between SiC particles and the larger alloy powder. Furthermore, the method of spraying NiCrSiBC alloy powder twice ensures that the SiC particles are well encapsulated within the NiCrSiBC alloy powder, resulting in a dense composite coating with low surface roughness. The purpose of using NiCrSiBC alloy powder in this invention is to utilize Ni-based metal catalysis to decompose SiC at temperatures far below its melting point. In addition, NiCrSiBC alloy is a nickel-based self-fluxing alloy with good wettability, wear resistance, corrosion resistance, and high-temperature self-lubricating properties. The purpose of using vacuum cladding and furnace cooling in this invention is to prevent oxidation of the coating during cladding in air, which would increase coating defects. Moreover, the slower heating and cooling rates ensure more complete reactions in the coating, reducing defects such as porosity and component segregation. In the high-temperature cladding step of the method of the present invention, thermal damage to the base material may occur due to the high cladding temperature. The method of the present invention designs a corresponding heat treatment process to address this problem, repair the performance reduction caused by high-temperature cladding, and remove the residual stress introduced during the preparation of the wear-resistant layer.

[0013] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) This invention utilizes the catalytic effect of Ni-based metals to decompose SiC particles at temperatures far below their melting points, generating in-situ various types and scales of carbide, boride, and silicide reinforcing phases. Under the combined effects of solid solution strengthening, grain refinement strengthening, and second-phase strengthening, the coating's hardness and wear resistance are improved by 8-15 times. Compared with technologies such as laser cladding, this invention has a lower cladding temperature and less damage to the substrate. The in-situ generated reinforcing phases have advantages such as thermodynamic stability, uniform distribution, clean interfaces, and good bonding with the coating substrate, effectively avoiding problems such as poor bonding strength and segregation of externally added reinforcements. The multi-type, multi-scale reinforcing phase structure overcomes the limitations of a single reinforcing phase. The multiple reinforcing phases complement each other, creating a "composite reinforcement effect" in the cladding layer, thereby solving problems such as mismatch in wear rate and reduced toughness between a single reinforcing phase and the coating substrate.

[0014] 2) The vacuum cladding technology used has a slower heating and cooling rate compared to laser cladding, resulting in less residual thermal stress and more complete reactions during the cladding process. Therefore, the resulting coating is uniform in composition, dense, and free of defects such as pores and cracks.

[0015] 3) The NiCrSiBC self-fluxing alloy powder used has good wettability with the steel substrate, excellent toughness and wear resistance, which can effectively improve the wear resistance of the coating and the bonding performance between the coating and the substrate. The main component of the alloy is Ni, which can accelerate the decomposition of SiC. At the same time, a large amount of carbophilic element Cr will promote the formation of hard carbide phases during the cladding process.

[0016] 4) The carburizing effect forms a gradient C diffusion layer on the surface of low carbon steel, and at the same time, cementite is generated at the interface, forming a strong chemical bond. This increases the bonding force between the coating and the low carbon steel interface, while also increasing the hardness at the interface by 2 to 5 times.

[0017] 5) The technical solution of this invention is simple, easy to implement, low in cost, and has good repeatability. It is suitable for industrial production and can effectively reduce the wear and failure problem of low carbon steel, thus broadening its application scope. Attached Figure Description

[0018] The accompanying drawings, which are provided to further illustrate the invention and form part of this application, illustrate exemplary embodiments of the invention and are used to explain the invention, but do not constitute an undue limitation of the invention.

[0019] Figure 1 This is a schematic cross-sectional view of the low-carbon steel matrix material to be reinforced in this invention.

[0020] Figure 2 This is a cross-sectional schematic diagram of the substrate material surface after an organic adhesive layer has been brushed onto it in this invention.

[0021] Figure 3 This is a cross-sectional schematic diagram of the substrate material surface after uniformly spraying SiC particles in this invention.

[0022] Figure 4 This is a schematic cross-sectional view of the substrate material surface after spraying two sizes of NiCrSiBC alloy powder on it, as described in this invention.

[0023] Figure 5 This is a cross-sectional schematic diagram of the alloy powder and SiC particles after the organic binder is brushed onto their surfaces again in this invention.

[0024] Figure 6 This is a schematic cross-sectional view of the surface of the second organic binder after spraying two sizes of NiCrSiBC alloy powder on it.

[0025] Figure 7This is a cross-sectional schematic diagram of a high-hardness wear-resistant coating containing multiple reinforcing phases and a carburized layer obtained on the surface of low-carbon steel after high-temperature cladding in this invention.

[0026] Figure 8 These are scanning electron microscope (SEM) images of the cross-sectional low-magnification (a) and high-magnification (b) microstructure of the high-hardness wear-resistant coating prepared in Example 1 of the present invention.

[0027] Figure 9 This is a metallographic micrograph of the high-hardness wear-resistant coating / substrate interface prepared in Example 1 of the present invention before heat treatment.

[0028] Figure 10 The mass loss results of the low carbon steel substrate material and the prepared high hardness wear-resistant coating in Example 1 of the present invention after being worn for 30 minutes at a speed of 300 r / min and a load of 45 N on a dry sand rubber wheel wear tester.

[0029] In the figure: 1-Low carbon steel substrate material, 2-Organic binder, 3-SiC particles, 4-1-Large-size NiCrSiBC alloy powder, 4-2-Small-size NiCrSiBC alloy powder, 5-High-hardness wear-resistant coating, 5-1-Carbide, 5-2-Bordide, 5-3-Silicide, 6-High-hardness carburized layer. Detailed Implementation

[0030] To enable those skilled in the art to better understand the present invention, the present invention will be further described clearly and completely below with reference to the accompanying drawings and embodiments, but is not limited to the following embodiments. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other. Example 1

[0031] A method for preparing a high-hardness wear-resistant coating on the surface of low-carbon steel based on SiC decomposition specifically includes the following steps: (1) Surface pretreatment of low-carbon steel: 16Mn steel was selected as the low-carbon steel substrate material 1. The surface of the low-carbon steel substrate material 1 was ground with sandpaper to remove the oxide layer and rust, and then cleaned with deionized water, acetone, alcohol, etc., to obtain a clean surface of the low-carbon steel substrate material 1, such as... Figure 1 As shown.

[0032] (2) SiC particle fixation: A layer of organic binder 2 is brushed onto the surface of the treated low-carbon steel matrix material 1, such as... Figure 2 As shown, SiC particles 3 with a particle size of 100 µm are then uniformly sprayed onto the surface of the low-carbon steel matrix material 1 for bonding and fixation. The amount of SiC particles 3 sprayed accounts for 5 wt.% of the total amount of SiC particles 3 and NiCrSiBC alloy powder. Figure 3 As shown.

[0033] (3) NiCrSiBC alloy powder fixation: Large-size NiCrSiBC alloy powder 4-1 (300 µm) and small-size NiCrSiBC alloy powder 4-2 (0.3 times the size of the large-size NiCrSiBC alloy powder 4-1) are sequentially sprayed onto the surface of the SiC particle 3 layer of the low-carbon steel matrix material 1 until the surface reaches its densest arrangement. Figure 4 As shown; then, organic binder 2 is brushed on again and large-size NiCrSiBC alloy powder 4-1 with a particle size of 300 µm and small-size NiCrSiBC alloy powder 4-2 with a particle size 0.3 times that of NiCrSiBC alloy powder 4-1 are sprayed in sequence. The proportion of NiCrSiBC alloy powder sprayed in the total amount of SiC particles 3 and NiCrSiBC alloy powder is 95 wt.%. Figure 5 and 6 As shown; The densest arrangement refers to the situation where no new large (small) NiCrSiBC alloy powder particle can be added between three or four adjacent large (small) NiCrSiBC alloy powder particles. The NiCrSiBC alloy powder is composed of the elements Ni, Cr, Si, B, Fe, and C, with Cr content of 5 wt.%, Si content of 3 wt.%, B content of 2 wt.%, C content of 0.05 wt.%, and Ni content of 89.95 wt.%.

[0034] (4) High-temperature cladding: The treated low-carbon steel substrate material 1 is placed in a vacuum heating device and clad at a temperature far below the melting point of SiC. The holding temperature of the vacuum heating is 1000 ℃ and the holding time is 40 min.

[0035] (5) Post-treatment: After furnace cooling, the low-carbon steel substrate 1 is quenched and tempered, and finally a high-hardness wear-resistant coating 5 containing multiple reinforcing phases such as carbides 5-1, borides 5-2, and silicides 5-3 is obtained on the surface of the low-carbon steel substrate 1. A high-hardness carburized layer 6 is formed at the interface between the high-hardness wear-resistant coating 5 and the low-carbon steel substrate 1, such as Figure 7 As shown.

[0036] Figure 8 The images show low-magnification (a) and high-magnification (b) microstructures of the cross-section of the high-hardness wear-resistant coating prepared in Example 1 of this invention. It can be seen from the images that the high-hardness wear-resistant coating 5 prepared by the method of this invention is dense and uniform, without defects such as pores and cracks, and the coating contains reinforcing phases of carbide 5-1, boride 5-2 and silicide 5-3 of various sizes and shapes. Figure 9The image shows a metallographic micrograph of the high-hardness wear-resistant coating / substrate interface prepared in Example 1 of the present invention before heat treatment. It can be seen from the image that the coating / substrate interface is well bonded, and the carbon in the coating diffuses into the substrate, forming a high-hardness carburized layer 6 at the interface, which is composed of large sheet pearlite and a small amount of ferrite. Figure 10 The figure shows the mass loss of the low-carbon steel substrate and the prepared high-hardness wear-resistant coating in Example 1 of this invention after being worn for 30 minutes at a speed of 300 r / min and a load of 45 N on a dry sand rubber wheel wear tester. It can be seen from the figure that the wear mass of the high-hardness wear-resistant layer prepared by the method of this invention is close to 1 / 17 of that of the low-carbon steel substrate, and it has excellent impact wear resistance. Example 2

[0037] A method for preparing a high-hardness wear-resistant coating on the surface of low-carbon steel based on SiC decomposition specifically includes the following steps: (1) Surface pretreatment of low-carbon steel: 16Mn steel was selected as the low-carbon steel substrate material 1. The surface of the low-carbon steel substrate material 1 was ground with sandpaper to remove the oxide layer and rust, and then cleaned with deionized water, acetone, alcohol, etc., to obtain a clean surface of the low-carbon steel substrate material 1, such as... Figure 1 As shown.

[0038] (2) SiC particle fixation: A layer of organic binder 2 is brushed onto the surface of the treated low-carbon steel matrix material 1, such as... Figure 2 As shown, SiC particles 3 with a particle size of 500 µm are then uniformly sprayed onto the surface of the low-carbon steel matrix material 1 for bonding and fixation. The amount of SiC particles 3 sprayed accounts for 2 wt.% of the total amount of SiC particles 3 and NiCrSiBC alloy powder. Figure 3 As shown.

[0039] (3) NiCrSiBC alloy powder fixation: Large-size NiCrSiBC alloy powder 4-1 (700 µm) and small-size NiCrSiBC alloy powder 4-2 (0.5 times the size of the large-size NiCrSiBC alloy powder 4-1) are sequentially sprayed onto the surface of the SiC particle 3 layer of the low-carbon steel matrix material 1 until the surface reaches its densest arrangement. Figure 4 As shown; then, organic binder 2 is brushed on again and large-size NiCrSiBC alloy powder 4-1 with a particle size of 700 µm and small-size NiCrSiBC alloy powder 4-2 with a particle size 0.5 times that of large-size NiCrSiBC alloy powder 4-1 are sprayed in sequence. The proportion of NiCrSiBC alloy powder sprayed in the total amount of SiC particles 3 and NiCrSiBC alloy powder is 98 wt.%. Figure 5 and 6 As shown; The densest arrangement refers to the situation where no new large (small) NiCrSiBC alloy powder particle can be added between three or four adjacent large (small) NiCrSiBC alloy powder particles. The NiCrSiBC alloy powder is composed of the elements Ni, Cr, Si, B, and C, with Cr content of 10 wt.%, Si content of 8 wt.%, B content of 7 wt.%, C content of 0.1 wt.%, and Ni content of 74.9 wt.%.

[0040] (4) High-temperature cladding: The treated low-carbon steel substrate material 1 is placed in a vacuum heating device and high-temperature cladding is carried out at a temperature far below the melting point of SiC. The holding temperature of vacuum heating is 1050 ℃ and the holding time is 20 min.

[0041] (5) Post-treatment: After furnace cooling, the low-carbon steel substrate 1 is quenched and tempered, and finally a high-hardness wear-resistant coating 5 containing multiple reinforcing phases such as carbides 5-1, borides 5-2, and silicides 5-3 is obtained on the surface of the low-carbon steel substrate 1. A high-hardness carburized layer 6 is formed at the interface between the high-hardness wear-resistant coating 5 and the low-carbon steel substrate 1, such as Figure 7 As shown. Example 3

[0042] A method for preparing a high-hardness wear-resistant coating on the surface of low-carbon steel based on SiC decomposition specifically includes the following steps: (1) Surface pretreatment of low-carbon steel: 16Mn steel was selected as the low-carbon steel substrate material 1. The surface of the low-carbon steel substrate material 1 was ground with sandpaper to remove the oxide layer and rust, and then cleaned with deionized water, acetone, alcohol, etc., to obtain a clean surface of the low-carbon steel substrate material 1, such as... Figure 1 As shown.

[0043] (2) SiC particle fixation: A layer of organic binder 2 is brushed onto the surface of the treated low-carbon steel matrix material 1, such as... Figure 2 As shown, SiC particles 3 with a particle size of 250 µm were then uniformly sprayed onto the surface of the low-carbon steel matrix material 1 for bonding and fixation. The amount of SiC particles 3 sprayed accounted for 8 wt.% of the total amount of SiC particles 3 and NiCrSiBC alloy powder. Figure 3 As shown.

[0044] (3) NiCrSiBC alloy powder fixation: Large-sized NiCrSiBC alloy powder 4-1 (50 µm) and small-sized NiCrSiBC alloy powder 4-2 (0.7 times the size of the large-sized NiCrSiBC alloy powder 4-1) are sequentially sprayed onto the surface of the SiC particle 3 layer of the low-carbon steel matrix material 1 until the surface reaches its densest arrangement. Figure 4As shown. Then, organic binder 2 is brushed on again, and large-size NiCrSiBC alloy powder 4-1 with a particle size of 50 µm and small-size NiCrSiBC alloy powder 4-2 with a particle size 0.7 times that of large-size NiCrSiBC alloy powder 4-1 are sprayed in sequence. The proportion of NiCrSiBC alloy powder sprayed in the total amount of SiC particles 3 and NiCrSiBC alloy powder is 92 wt.%. Figure 5 and 6 As shown; The densest arrangement refers to the situation where no new large (small) NiCrSiBC alloy powder particle can be added between three or four adjacent large (small) NiCrSiBC alloy powder particles. The NiCrSiBC alloy powder is composed of the elements Ni, Cr, Si, B, Fe, and C, with Cr content of 8 wt.%, Si content of 6 wt.%, B content of 4 wt.%, C content of 0.08 wt.%, and Ni content of 81.92 wt.%.

[0045] (4) High-temperature cladding: The treated low-carbon steel substrate material 1 is placed in a vacuum heating device and clad at a temperature far below the melting point of SiC. The holding temperature of the vacuum heating is 1150 ℃ and the holding time is 5 min.

[0046] (5) Post-treatment: After furnace cooling, the low-carbon steel substrate 1 is quenched and tempered, and finally a high-hardness wear-resistant coating 5 containing multiple reinforcing phases such as carbides 5-1, borides 5-2, and silicides 5-3 is obtained on the surface of the low-carbon steel substrate 1. A high-hardness carburized layer 6 is formed at the interface between the high-hardness wear-resistant coating 5 and the low-carbon steel substrate 1, such as Figure 7 As shown.

[0047] The above provides a clear and complete description of the technical solutions in the embodiments of the present invention. The described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

Claims

1. A method for preparing a high-hardness wear-resistant coating on the surface of low-carbon steel based on SiC decomposition, characterized in that, Includes the following steps: (1) Surface pretreatment of low carbon steel: Grind the surface of low carbon steel with sandpaper to remove oxide layer and rust, and clean it with deionized water, acetone or alcohol to obtain a clean surface of low carbon steel substrate material. (2) SiC particle fixation: A layer of organic adhesive is brushed onto the surface of the low carbon steel substrate material, and then SiC particles are evenly sprayed onto the surface of the low carbon steel substrate material and bonded and fixed with the organic adhesive. (3) NiCrSiBC alloy powder fixation: Spray two types of NiCrSiBC alloy powder of different sizes onto the surface of the SiC particle layer until the surface is densest; then continue to brush on a layer of organic binder, and spray two types of NiCrSiBC alloy powder of different sizes again to achieve the densest arrangement. (4) High-temperature cladding: The treated low-carbon steel substrate material is placed in a vacuum heating device and clad at a temperature lower than the melting point of SiC. The heat preservation temperature of the vacuum heating device is 1000~1150 ℃ and the heat preservation time is 5 min~40 min. (5) Post-treatment: After furnace cooling, the low carbon steel substrate material is quenched and tempered respectively, and finally a high hardness wear-resistant coating containing multiple reinforcing phases is obtained on the surface of the low carbon steel substrate material.

2. The method for preparing a high-hardness wear-resistant coating on a low-carbon steel surface based on SiC decomposition according to claim 1, characterized in that: In step (2), the particle size of SiC particles is 100 µm to 500 µm, and the amount of SiC particles sprayed accounts for 2 to 8 wt.% of the total amount of SiC particles and NiCrSiBC alloy powder.

3. The method for preparing a high-hardness wear-resistant coating on a low-carbon steel surface based on SiC decomposition according to claim 1, characterized in that: In step (3), the particle size of the large-size NiCrSiBC alloy powder is 50 µm to 700 µm, the particle size of the small-size NiCrSiBC alloy powder is 0.3 to 0.7 times that of the large-size alloy powder, and the proportion of NiCrSiBC alloy powder sprayed in the total amount of SiC particles and NiCrSiBC alloy powder is 92 to 98 wt.

4. The method for preparing a high-hardness wear-resistant coating on a low-carbon steel surface based on SiC decomposition according to claim 1 or 3, characterized in that: NiCrSiBC alloy powder is composed of elements Ni, Cr, Si, B, and C, with Cr content of 5~10 wt.%, Si content of 3~8 wt.%, B content of 2~7 wt.%, C content of 0.05~0.1 wt.%, and Ni content of 74.9~89.95 wt.%.

5. The method for preparing a high-hardness wear-resistant coating on the surface of low-carbon steel based on SiC decomposition according to claim 1, characterized in that: In step (3), the densest arrangement means that no new NiCrSiBC alloy powder particle can be added between three or four adjacent NiCrSiBC alloy powder particles.

Citation Information

Patent Citations

  • Alloy powder for laser cladding in-situ generation and cladding layer prepared by using powder

    CN115404476A

  • Diamond reinforced wear-resistant layer with uniformly arranged diamond particle clusters and preparation method of diamond reinforced wear-resistant layer

    CN115287651A